- Thread starter
- #1

Is this correct?

$$

\text{B.C.}=\begin{cases}

T_x(0,t) = 0\\

T(\pi,t) = 1

\end{cases}

$$

The I.C. is $T(x,0) = 0$.

The equation is $\frac{1}{\alpha}T_t = T_{xx}$.$$

\varphi(x) = A\cos\lambda x + B\frac{\sin\lambda x}{\lambda}

$$

and

$$

\psi(t) = C\exp\left(-\alpha\lambda^2t\right).

$$

First, let's solve the steady state solution, $\varphi_{\text{ss}}'' = 0\Rightarrow\varphi_{\text{ss}} = ax + b$.

From the boundary conditions, we have that $\varphi_{\text{ss}}' = a = 0$ and $\varphi_{\text{ss}} = b = 1$.

So

$$

\varphi_{\text{ss}}(x) = 1

$$

which satisfy both boundary conditions.

Next, let's solve the transient problem.

Then we have that $\varphi' = -\lambda A\sin\lambda x + B\cos\lambda x$.

Using the homogeneous boundary condition, we have that $B = 0$.

So we are left with $\varphi(x) = A\cos\lambda x$.

Next, we have

$$

\cos\lambda L = 0\Rightarrow\lambda = \left(n + \frac{1}{2}\right)\frac{\pi}{L},\quad n\in\mathbb{Z}^+.

$$

Our general solution is of the form

$$

T(x,t) = 1 + \sum_{n = 1}^{\infty}A_n\cos\left[\left(n + \frac{1}{2}\right)\frac{\pi x}{L}\right]\exp\left[-\alpha\left(n + \frac{1}{2}\right)^2\frac{\pi^2}{L^2}t\right].

$$

Using the initial condition, we have $\int_0^{\pi}[f(x) - 1]\cos\left[\left(n + \frac{1}{2}\right)\frac{\pi x}{L}\right]dx = \frac{L}{2}A_n\iff A_n = (-1)^n\frac{4}{\pi(2n + 1)}$.

Finally, we have that the solution to heat equation with the prescribed is

$$

T(x,t) = 1 + \frac{4}{\pi}\sum_{n = 1}^{\infty}\frac{(-1)^n}{2n + 1}\cos\left[\left(n + \frac{1}{2}\right)\frac{\pi x}{L}\right]\exp\left[-\alpha\left(n + \frac{1}{2}\right)^2\frac{\pi^2}{L^2}t\right].

$$

For the special case of when $\alpha = 1$ and $L = \pi$, we have

$$

T(x,t) = 1 + \frac{4}{\pi}\sum_{n = 1}^{\infty}\frac{(-1)^n}{2n + 1}\cos\left[\left(n + \frac{1}{2}\right)x\right]\exp\left[-\left(n + \frac{1}{2}\right)^2t\right].

$$

$$

\text{B.C.}=\begin{cases}

T_x(0,t) = 0\\

T(\pi,t) = 1

\end{cases}

$$

The I.C. is $T(x,0) = 0$.

The equation is $\frac{1}{\alpha}T_t = T_{xx}$.$$

\varphi(x) = A\cos\lambda x + B\frac{\sin\lambda x}{\lambda}

$$

and

$$

\psi(t) = C\exp\left(-\alpha\lambda^2t\right).

$$

First, let's solve the steady state solution, $\varphi_{\text{ss}}'' = 0\Rightarrow\varphi_{\text{ss}} = ax + b$.

From the boundary conditions, we have that $\varphi_{\text{ss}}' = a = 0$ and $\varphi_{\text{ss}} = b = 1$.

So

$$

\varphi_{\text{ss}}(x) = 1

$$

which satisfy both boundary conditions.

Next, let's solve the transient problem.

Then we have that $\varphi' = -\lambda A\sin\lambda x + B\cos\lambda x$.

Using the homogeneous boundary condition, we have that $B = 0$.

So we are left with $\varphi(x) = A\cos\lambda x$.

Next, we have

$$

\cos\lambda L = 0\Rightarrow\lambda = \left(n + \frac{1}{2}\right)\frac{\pi}{L},\quad n\in\mathbb{Z}^+.

$$

Our general solution is of the form

$$

T(x,t) = 1 + \sum_{n = 1}^{\infty}A_n\cos\left[\left(n + \frac{1}{2}\right)\frac{\pi x}{L}\right]\exp\left[-\alpha\left(n + \frac{1}{2}\right)^2\frac{\pi^2}{L^2}t\right].

$$

Using the initial condition, we have $\int_0^{\pi}[f(x) - 1]\cos\left[\left(n + \frac{1}{2}\right)\frac{\pi x}{L}\right]dx = \frac{L}{2}A_n\iff A_n = (-1)^n\frac{4}{\pi(2n + 1)}$.

Finally, we have that the solution to heat equation with the prescribed is

$$

T(x,t) = 1 + \frac{4}{\pi}\sum_{n = 1}^{\infty}\frac{(-1)^n}{2n + 1}\cos\left[\left(n + \frac{1}{2}\right)\frac{\pi x}{L}\right]\exp\left[-\alpha\left(n + \frac{1}{2}\right)^2\frac{\pi^2}{L^2}t\right].

$$

For the special case of when $\alpha = 1$ and $L = \pi$, we have

$$

T(x,t) = 1 + \frac{4}{\pi}\sum_{n = 1}^{\infty}\frac{(-1)^n}{2n + 1}\cos\left[\left(n + \frac{1}{2}\right)x\right]\exp\left[-\left(n + \frac{1}{2}\right)^2t\right].

$$

Last edited: